Variability in mental health reporting among refugees and migrants in need of protection: new evidence from a weekly panel survey - Abigail, Weitzman (2023)
Background: The global population of refugees and other migrants in need of protection (MNP) is swiftly growing. Prior scholarship highlights that MNP have poorer mental health than other migrant and non-migrant populations. However, most scholarship on MNP mental health is cross-sectional, leaving open questions about temporal variability in their mental health. Methods: Leveraging novel weekly survey data from Latin American MNP in Costa Rica, we describe the prevalence, magnitude, and frequency of variability in eight indicators of self-reported mental health over 13-weeks; highlight which demographic characteristics, incorporation hardships, and violence exposures are most predictive of variability; and determine how variability corresponds to baseline mental health. Results: For all indicators, most respondents (> 80%) varied at least occasionally. Typically, respondents varied 31% to 44% of weeks; for all but one indicator they varied widely—by ~ 2 of 4 possible points. Age, education, and baseline perceived discrimination were most consistently predictive of variability. Hunger and homelessness in Costa Rica and violence exposures in origin also predicted variability of select indicators. Better baseline mental health was associated with less subsequent variability. Conclusions: Our findings highlight temporal variability in repeated self-reports of mental health among Latin American MNP and further highlight sociodemographic heterogeneity therein.